Computational screen of M2P metal phosphides for catalytic ethane dehydrogenation. Issue 18 (9th August 2022) - Ko, Jeonghyun; Schneider, William F.
Abstract : Metal phosphide screening for ethane dehydrogenation. Abstract : Metal phosphides are promising catalysts for hydrocarbon transformations, but computational screening is complicated by their diverse structures and compositions. To disentangle structural from compositional contributions, here we explore the metal-rich M2 P (M = Fe, Co, Ni, Cu, Mo, Ru, Rh, Pd, Ag, Pt) series in hexagonal and orthorhombic structures that are common to a subset of these materials, using supercell density functional theory (DFT). To understand the contribution of metal choice to utility for catalytic ethane dehydrogenation (EDH), we compute and compare the adsorption of key EDH intermediates across low-index surface terminations. These materials expose both metal and phosphide sites. Calculations show that binding energies at metal sites correlate with the bulk metals, with P incorporation either enhancing or suppressing binding. Phosphide sites compete with metal sites for adsorbates and tend to suppress overactivation by destabilizing highly dehydrogenated species engaging in C–H bond breaking. Results are generally insensitive to bulk structure and surface facet. Results suggest metal-rich Pd phosphides to have favorable adsorption characteristics for catalytic dehydrogenation, consistent with recent observations.